Comparison of 18FDG-PET/CT and conventional follow-up methods in colorectal cancer: A randomised prospective study. Issue 2 (February 2021) - Monteil, Jacques; Le Brun-Ly, Valerie; Cachin, Florent; Zasadny, Xavier; Seitz, Jean-François; Mundler, Olivier; Selvy, Marie; Smith, Denis; Rullier, Eric; Lavau-Denes, Sandrine; Lades, Guillaume; Labrunie, Anais; et al.
Abstract: Background: A surveillance program was performed in colorectal cancer (CRC) patients after surgery, to diagnose asymptomatic recurrence. Aims: To assess whether 18-FDG positron emission tomography/CT (PET/CT) improved the detection of recurrence during a 3-year follow-up. Methods: A multicentre, two-arm randomised prospective trial comparing different 36-month follow-up strategies. Complete colonoscopy was performed at baseline and after 3 years and clinical exams with imaging every 3 months. The conventional arm (A) received carcinoembryonic antigen, liver echography, and alternated between lung radiography and computed tomography (CT) scans. The experimental arm (B) received PET/CT. Results: A total of 365 patients with colon (79.4%) or rectal cancer (20.6%), stages II (48.2%) or III (50.8%), were enroled in this study. At 36 months, intention-to-treat analysis revealed recurrence in 31 (17.2%) patients in arm A and 47 (25.4%) in arm B ( p  = 0.063). At 3 years, 7 of 31 relapses (22.5%) in arm A were surgically treated with curative intent, compared to 17 of 47 (36.2%) in arm B ( p  = 0.25). The rates of recurrence and new cancers were higher in arm B than arm A (p = 0.038). Conclusions: PET/CT follow-up every 6 months did not increase the rate of recurrence at 3 years or the rate of surgically treated recurrence compared with conventional follow-up.